Intra-Party Leadership Contests and Effect on Levels of Satisfaction with Democracy on Party Voters - Katsourides, Yiannos; Ioannidis, Nikandros (My University, 2025)
This article investigates the relationship between intra-party leadership contestations on levels of satisfaction with democracy among party voters, trying to identify the impact of the former on the latter. The article draws on empirical data for a cross-sectional analysis from three different data sets that cover 11 countries, including a more case-specific analysis that utilizes panel data from Germany. Overall, the study aims to capture the dynamics of intra-party politics and the magnitude of its effect on perceptions of democracy among parties' voters. We find that intra-party politics at its probably most competitive version, that is elections for the head of the party, does not seem to exercise any significant influence on voters' satisfaction with democracy.
Keywords: political parties; democracy; intra-party elections; party leaders; competitiveness